THE EFFECT OF SCHOOL LEADERSHIP EFFECTIVENESS ON TEACHER PERFORMANCE ( A Case Study at SMP Negeri Kota Singkawang) - M.Thaiyibi (IJGIE (International Journal of Graduate of Islamic Education), 2020)
This survey study aims to understand effective secondary school leadership towards improving teacher performance in the teaching and learning process. There is no doubt that effective school principals are able to promote faster education improvement. On the other hand, good school leadership has a strong impact on school development and student learning outcomes. To understand how the effectiveness of school leadership on teacher performance, survey research has been successfully carried out in Singkawang City Middle School. The results showed that a very successful educational leadership can influence the whole school community especially teachers and students to achieve higher performance in school organizations. This research proves that the principal's strong leadership can not only influence teachers in teaching but also students in learning as a whole. Therefore, similar research can continue to be carried out so that effective educational leadership can influence the people he dreams of with a high commitment to improve work performance such as teachers, school development and surrounding resident